Read at Home: More Level 3a : Missing! - Roderick Hunt (Oxford, United Kingdom Oxford University Press, 2006)
Read at Home is the best-selling home reading series designed for young, beginner readers. It features all the popular Oxford Reading Tree characters in exciting stories specially written for parents to support their children's reading at home. These entertaining stories, with real life and fantasy adventures, are carefully graded across 5 levels, and contain built-in progression and vocabulary repetition throughout. Missing is Level 3a for children Becoming a Reader - those children who can recognize 10-20 words by sight, can read simple sentences, and know all the initial letter sounds. The story is written with a simple sentence structure and vocabulary repetition with two to three sentences per page. Stories provide clear parental support within and beyond the book: BLa "Tips for Reading Together" page, giving parents practical ideas for helping with their child's reading BLa "Think about the Story" page providing stimulating ideas for parents to talk about with children when they are discussing the story...
Keywords: Read Aloud -- Independent Reading